Bài 1:Phân tích đa thức thành nhân tử: a. x^3+6x^2+11x+6 b. P(x)=x^4-8x^2-x+12 Bài 2: Chứng minh rằng: (x^2+y^2)/2 ≥ ((x+y)/2)^2

Question

Bài 1:Phân tích đa thức thành nhân tử:
a. x^3+6x^2+11x+6
b. P(x)=x^4-8x^2-x+12
Bài 2:
Chứng minh rằng:
(x^2+y^2)/2 ≥ ((x+y)/2)^2

in progress 0
Reese 2 tuần 2021-07-10T11:37:40+00:00 2 Answers 1 views 0

Answers ( )

    0
    2021-07-10T11:38:57+00:00

    Đáp án:

     

    Giải thích các bước giải:

     

    0
    2021-07-10T11:39:09+00:00

    Bài 1:

    a. $x^3+6x^2+11x+6=x^3+1+6x^2-6+11x+11$

    $=(x+1)(x^2-x+1)+6(x+1)(x-1)+11(x+1)$

    $=(x+1)(x^2-x+1+6x-6+11)=(x+1)(x^2+5x+6)$

    $=(x+1)(x+2)(x+3)$

    b. $P(x)=x^4-8x^2-x+12$

              $=x^4-7x^2+\frac{49}{4}-x^2-x-\frac{1}{2}$

              $=(x^2-\frac{7}{2})^2-(x+\frac{1}{2})^2$

              $=(x^2+x-3)(x^2-x-4)$

              $=(x-\frac{-1+\sqrt[]{13}}{2})(x-\frac{-1-\sqrt[]{13}}{2})(x-\frac{1+\sqrt[]{17}}{2})(x-\frac{1+\sqrt[]{17}}{2})$

    Bài 2:

    Xét $2(x^2+y^2)-(x+y)^2=2x^2+2y^2-(x^2+2xy+y^2)$

    $=x^2-2xy+y^2=(x-y)^2≥0$

    Vậy $ 2(x^2+y^2)-(x+y)^2≥0$

    ⇔ $x^2+y^2≥$$\frac{(x+y)^2}{2}$ 

    ⇔ $\frac{x^2+y^2}{2}≥$$\frac{(x+y)^2}{2}$ 

    Dấu “=” xảy ra khi $x-y=0$ ⇔ $x=y$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )